IMPACT OF GOOD CORPORATE GOVERNANCE TOWARDS CORPORATE VALUE WITH ENTERPRISE RISK MANAGEMENT AS MODERATING VARIABLE (EMPIRICAL STUDY OF FINANCIAL COMPANIES LISTED IN IDX FOR THE PERIOD 2017-2019) - Lydia Sibarani; Herlina Lusmeida (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- This research aims to observe and analyze the impact of Good Corporate Governance towards Corporate Value as well as analyzing whether Enterprise Risk Management is able to moderate its impact. Good Corporate Governance is proxied by the presence of Independent Commissioners, Audit Committee, as well as Managerial Ownership. The population of this research includes all financial companies that publish their annual report in Bursa Efek Indonesia (BEI) over the period of 2017-2019. Data were analyzed using the multiple regression method and the moderated regression analysis. The result of this research found that Independent Commissioners and Audit Committee gives positive and significant impact towards Corporate Value while Managerial Ownership gives negative and insignificant impact towards Corporate Value. Enterprise Risk Management is not able to moderate the impact of Independent Commissioner and Managerial Ownership towards Corporate Value but is able to moderate the impact of the Audit Committee towards Corporate Value. Keywords: Audit Committee; Corporate Value; Corporate Governance; Independent Commissioner; Managerial Ownership